Analisis Faktor Lingkungan Kerja, Pelatihan & Pengawasan Terhadap Penerapan K3 Pada Pekerja Kontraktor Drilling Well Intervention Pt Xyz - Adam, Ichsan; Erislan, Erislan; Ramli, Soehatman (Syntax Literate, 2026)
Background: Occupational Health and Safety (OHS) remains a critical concern in the oil and gas industry. The International Labour Organization (ILO) recorded nearly three million work-related deaths globally in 2023, while Indonesia reported 370,747 occupational accident cases in the same year. Drilling and well intervention operations at PT XYZ present particularly high-risk environments demanding strict OHS compliance. Objective: This study aims to analyze the influence of work environment, training, and supervision on OHS implementation among contractor workers in drilling and well intervention operations at PT XYZ. Method: A quantitative approach with a correlative analytical design and cross-sectional method was employed. The population consisted of 100 contractor workers at Zona Rokan North DSF, with 80 respondents selected for the main study using total sampling. Data were collected through structured questionnaires using a five-point Likert scale and analyzed using multiple linear regression with SPSS. Results: Work environment significantly influenced OHS implementation (B=0.435, p=0.003). Training demonstrated the strongest effect (B=0.560, p=0.0001), while supervision showed no significant partial influence (B=-0.034, p=0.755). Simultaneously, all three variables significantly influenced OHS implementation (F=14.736, p=0.0001). Conclusion: Training is the most dominant factor in improving OHS compliance, followed by work environment. Although supervision did not show a significant partial effect, its combination with other factors remains essential. Companies must adopt a comprehensive and integrated approach optimizing work conditions, strengthening competency-based training, and reinforcing safety culture to achieve optimal OHS compliance in high-risk oil and gas operations.